Analisis Faktor Internal dan Eksternal pada Unit Pengolahan Teh Rakyat Kelompok Tani Barokah, Bandung - Tammah, Siti Utami; Trimo, Lucyana (Politeknik Negeri Lampung, 2018)
The tea plantation area in Indonesia is still dominated by tea smallholder estate of 45,17%. This is accompanied also by the growing number of tea agroindustry which increased by 0,83% based on data from the ministry of industry period 2007 to 2013. One of the tea agroindustry that still survive is tea smallholder processing unit of Barokah Farmer Group in Lebak Muncang Village, District Ciwidey Regency Bandung. This study aims to analyze the internal and external factors of the tea smallholder processing units of Barokah Farmer Group. The technique used in this research is case study with the informants include the management of the in tea smallholder processing units in Barokah Farmer Group, the government agency of Bandung Plantation Office. The technique of data collection is done by observation, in-depth interview and documentation. The analysis tools used are IFE Analysis (internal factors evaluation) and EFE (external factor evaluation). The results showed that tea smallholder agro industry of Barokah Farmer Group has a strong internal position where the strengths that have been able to cover the weakness well but have not been able to exploit the opportunities optimally and become very vulnerable to the threat of competition so that tea smallholder agro industry of Barokah Farmer Group is weak in facing the dynamics of the external environment. Keywords: agroindustry, tea smallholder, tea processing unit